11.2k views
1 vote
Find the general solution to 1/x dy/dx - 2y/x^2 = x cos x, y(pi) = pi^2

User Rengas
by
6.2k points

1 Answer

5 votes

Answer:


(y)/(x^2)=\sin x+\pi

Explanation:

Consider linear differential equation
\frac{\mathrm{d} y}{\mathrm{d} x}+yp(x)=q(x)

It's solution is of form
y\,I.F=\int I.F\,q(x)\,dx where I.F is integrating factor given by
I.F=e^(\int p(x)\,dx).

Given:
(1)/(x)\frac{\mathrm{d} y}{\mathrm{d} x}-(2y)/(x^2)=x\cos x

We can write this equation as
\frac{\mathrm{d} y}{\mathrm{d} x}-(2y)/(x)=x^2\cos x

On comparing this equation with
\frac{\mathrm{d} y}{\mathrm{d} x}+yp(x)=q(x), we get
p(x)=(-2)/(x)\,\,,\,\,q(x)=x^2\cos x

I.F =
e^(\int p(x)\,dx)=e^{\int (-2)/(x)\,dx}=e^(-2\ln x)=e^{\ln x^(-2)}=(1)/(x^2) { formula used:
\ln a^b=b\ln a }

we get solution as follows:


(y)/(x^2)=\int (1)/(x^2)x^2\cos x\,dx\\(y)/(x^2)=\int \cos x\,dx\\\\(y)/(x^2)=\sin x+C

{ formula used:
\int \cos x\,dx=\sin x }

Applying condition:
y(\pi)=\pi^2


(y)/(x^2)=\sin x+C\\(\pi^2)/(\pi)=\sin\pi+C\\\pi=C

So, we get solution as :


(y)/(x^2)=\sin x+\pi

User Zindorsky
by
5.6k points